2019
DOI: 10.1128/aem.00334-19
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella enterica in Soils Amended with Heat-Treated Poultry Pellets Survived Longer than Bacteria in Unamended Soils and More Readily Transferred to and Persisted on Spinach

Abstract: Untreated biological soil amendments of animal origin (BSAAO) are commonly used as biological fertilizers but can harbor foodborne pathogens like Salmonella enterica, leading to potential transfer from soils to fruits and vegetables intended for human consumption. Heat-treated poultry pellets (HTPP) can provide produce growers with a slow-release fertilizer with a minimized risk of pathogen contamination. Little is known about the impact of HTPP-amended soil on the survival of Salmonella enterica. The contribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 49 publications
5
22
0
1
Order By: Relevance
“…As such, additional studies with a larger number of samples are needed to determine if these findings are reproducible; as well as test other factors such as, different soil-types (e.g., true sand and loam), irrigation practices (e.g., flood and dry-land production), and soil amendments (e.g., bovine and horse). Despite these limitations, this study is consistent with past research (using single strains, or cocktail; You et al, 2006;Semenov et al, 2009;Andino and Hanning, 2015;Underthun et al, 2018;Harrand et al, 2019;Shah et al, 2019), and also shows the variability of Salmonella strains under different agricultural parameters. Data and findings generated here can be used in (i) future risk assessments, (ii) selection of strains for future challenge and validation studies, especially when used together with whole genome sequencing data that may characterize the molecular determinants for environmental adaptation and survival (e.g., worst case contamination scenarios), and (iii) identification of best practices for application of BSAAO, like poultry litter, to agricultural fields.…”
Section: Resultssupporting
confidence: 91%
“…As such, additional studies with a larger number of samples are needed to determine if these findings are reproducible; as well as test other factors such as, different soil-types (e.g., true sand and loam), irrigation practices (e.g., flood and dry-land production), and soil amendments (e.g., bovine and horse). Despite these limitations, this study is consistent with past research (using single strains, or cocktail; You et al, 2006;Semenov et al, 2009;Andino and Hanning, 2015;Underthun et al, 2018;Harrand et al, 2019;Shah et al, 2019), and also shows the variability of Salmonella strains under different agricultural parameters. Data and findings generated here can be used in (i) future risk assessments, (ii) selection of strains for future challenge and validation studies, especially when used together with whole genome sequencing data that may characterize the molecular determinants for environmental adaptation and survival (e.g., worst case contamination scenarios), and (iii) identification of best practices for application of BSAAO, like poultry litter, to agricultural fields.…”
Section: Resultssupporting
confidence: 91%
“…A higher proportion of positive samples for Salmonella Typhimurium compared with Salmonella Enteritidis from the enriched samples further proved that the viability of Salmonella Enteritidis strain was more susceptible to changes in temperature, water activity and moisture level. A positive correlation between the CFU and PMAxx TM -based qPCR data obtained in the current study is in agreement with the findings of Shah et al (2019) who quantified the viable count of Salmonella Newport through a culture method and PMA-qPCR from heat treated poultry amended soil. A sharp decline in the survivability of both the serovars after 1 week of incubation at 37 • C was due to a significantly higher loss of moisture and water activity at this temperature.…”
Section: Discussionsupporting
confidence: 92%
“…In the current study, keeping the moisture level around 15% was to simulate real field conditions where the temperature in summer in South Australia can reach up to 45 • C with moisture level quite low. A higher moisture content favors the survivability of bacteria (Cools et al, 2001), where Salmonella Newport can survive in soil for longer periods (Shah et al, 2019). The Salmonella Enteritidis strain used in this study was isolated from a commercial egg farm.…”
Section: Discussionmentioning
confidence: 99%
“…L. monocytogenes was responsible for one of the deadliest foodborne outbreaks in U. S. history when 147 individuals fell ill and 33 died from eating contaminated cantaloupe in 2011 [5]. Recent work has shown that S. Newport can survive and potentially grow in simulated agricultural runoff [6]which may be present in river waters used for irrigation, and be introduced through runoff to soils amended with biological amendments and transfer to growing spinach plants in pre-harvest environments [7]. The potential presence of L. monocytogenes in surface irrigation waters can contaminate melons, and if introduced to cantaloupes, can survive at high levels depending on post-harvest storage temperature [8].…”
Section: Introductionmentioning
confidence: 99%